1.(2y−3)^2=10y-1​ 2.1/3c^2=(c-4)(c-6) ПОМОГИТЕ МНЕЕЕЕ

0 голосов
48 просмотров

1.(2y−3)^2=10y-1​
2.1/3c^2=(c-4)(c-6)
ПОМОГИТЕ МНЕЕЕЕ


Алгебра (695 баллов) | 48 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

4y^2–12y+9–10y+1=0
4y^2–22y+10=0
Д=/484–4•4•10=/324=18
х1=(22+18)/8=5
х2=(22–18)/8=1/2

1/3с^2=с^2–6с–4с+24
-2/3с^2+10с–24=0
Д=/100–4•(-2/3)•(-24)=/36=6
х1=(-10+6)/(-4/3)=3
х2=(-10–6)/(-4/3)=12

(15.0k баллов)
0

как получилось 12у??

0

а все, спасибо вам)

0

Пожалуйста) удачи на учебе!;)